Rapeseed peptide inhibits HepG2 cell proliferation by regulating the mitochondrial and P53 signaling pathways. (10th October 2022) - Ma, Keer; Wang, Zhigao; Ju, Xingrong; Huang, Jiankang; He, Rong
Abstract: Background: Rapeseed peptide, extracted from rapeseed protein, is known to have a variety of biological activities. In this study, the anti‐proliferation effect and molecular mechanism of rapeseed peptide on HepG2 cells were investigated. Results: In vitro anticancer experiments showed that the rapeseed peptide NDGNQPL could inhibit HepG2 cell proliferation in a concentration‐dependent manner [half maximal inhibitory concentration (IC50 ), 1.56 mmol L −1 ). HepG2 cells were induced by NDGNQPL at a 0.5 mmol L −1 concentration and exhibited a 28.39 ± 0.80% apoptosis rate and a cell cycle arrest in the G0/G1 phase. Meanwhile, rapeseed peptide induced a decrease in mitochondrial membrane potential, an increase in reactive oxygen species (ROS) release, and changes in the nuclear morphology of HepG2 cells, indicating that rapeseed peptide could induce cell apoptosis through the mitochondrial pathway. In addition, rapeseed peptide activated the proliferation‐related P53 signaling pathway, in which the expression levels of P53, P21, and cleaved‐caspase3 were up‐regulated, while the expression levels of murine double minute 2 (MDM2) were down‐regulated. In molecular docking simulations, NDGNQPL exhibited a good affinity for the MDM2 molecule, which supported the notion that the rapeseed peptide is able to inhibit MDM2, a negative regulator of P53. Conclusion: The current results indicate that the rapeseed‐derived NDGNQPL peptide has the potential to inhibit the proliferation of HepG2 cells and promote human health. © 2022 Society of Chemical Industry.